Climate Smart City: New Cultural Political Economies in the Making in Malmö, Sweden. Issue 6 (2nd November 2021) - Bulkeley, Harriet; Stripple, Johannes
ABSTRACT: The question of how the urgent transformation in fossil fuel based economies might be realised has come to occupy an increasingly prominent place within the social sciences. The challenge here is often cast in terms of how one or more existing system can be replaced by alternatives in which the carbon content has been removed or at least diluted by purposeful interventions. Here we approach the question from a different angle, asking how ongoing transformations in critical systems (in this case energy) are or may be leveraged in relation to climate change. We take as our focus the emergence of the smart city and examine a case in which the notion of the smart city has become wedded to the ambition for a low carbon city: Malmö, Sweden. As commentators suggest, the growth of the smart city reflects a capitalist reflex to develop new waves of investment to realise new arenas for capital accumulation in the city. Yet shifting from this broad political economy diagnosis, we argue that there is a need to attend to the ways in which climate is imbued and embedded in the smart city and how this in turn enables and constrains low carbon transitions.